A Theoretical Analysis of the Preventive Role of English as a Foreign Language Teachers’ Occupational Adjustment and Psychological Hardiness in Their Job Burnout - Li, Xiaoying (Frontiers in Psychology, 2022)
Teaching has long been considered as one of the most challenging professions worldwide due to the involvement of numerous linguistic, socio-political, social, and psych-emotional factors. Because of these factors, english as a foreign language (EFL) teachers are psychologically, emotionally, and physically pressed in their job. These damaging pressures often result in negative academic outcomes for teachers, students, and educational systems. Despite dire consequences, few studies (if any) have examined the role of psycho-emotional factors in improving teaching performance and reducing negative emotions at the workplace. To fill this gap, this mini-review article aimed to present a theoretical analysis of three constructs of occupational adjustment, psychological hardiness, and burnout. In so doing, the definitions, conceptualizations, dimensions, and empirical studies related to each variable were presented. The study ends with the existing research gaps and offers some implications for EFL teachers and other stakeholders by increasing their knowledge of emotions in occupational environments and the consequences that such emotions can have for an organization.